Pregnancy With Congenital Abnormalities from Marriage of a Different Ethnic: a Very Rare Case - Dalimunthe, Sofyan Qadri Rozi; Maharani, Cut Rika (Ridwan Institute, 2025)
Bladder exstrophy (BE) is one of the rare congenital abnormalities. This congenital disorder is also serious, with characteristics such as a spectrum of disorders involving the walls of the ventral body, the urogenital tract, the pelvis, the spine, and the anus. The incidence rate of this case is 1 per 30,000 to 50,000 live births. The case study reported the findings of congenital bladder extrophy in a 29-year-old Acehnese woman married to an Indian citizen, with a diagnosis of G3P0A2 38-39 weeks pregnant, coming with complaints. The mother felt the discharge of water. The patient admitted to being 9 months pregnant with HPHT 27/1/2021 and TTP 3/11/21 according to the gestational age of 38-39 weeks. The patient has a history of the disease with type 2 diabetes mellitus. Initial laboratory examination findings showed hyperglycemia at 256 mg/dL. Ultrasound examination found a single head presentation of the fetus alive with a mass in the abdomen of the fetus. The patient is planning to have an emergency cesarean section and is consulted by the internal medicine department for blood sugar regulation. Postpartum findings in infants with hernia, umbilical cord, Bladder Exstrophy, epispadia, and symphysiolysis will be consulted to the Division of Pediatric Surgery. This case report describes a pregnancy with congenital abnormalities and Bladder Exstrophy. Prenatal diagnosis allows the medical team to prepare for a multispecialty approach. It also gives parents time to prepare and adjust to expectations related to labor and the neonatal period, as well as potential complications and long-term prognosis.